Method for catalytically synthesizing diamond nanosheets under normal pressure and application of diamond nanosheets
By using two-dimensional titanium carbide and Ni metal powder prepression, argon heating and chlorine etching reaction under normal pressure, combined with air oxidation purification, the complex and unstable experimental problems in the preparation of diamond nanosheets were solved, and the problem of implementation was achieved The method of synthesizing stable diamond nanosheets under mild conditions has simple process and low cost characteristics.
Patent Information
- Application Number
- CN202411283798.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-13
- Publication Date
- 2024-12-17
AI Technical Summary
The existing diamond nanosheet preparation methods have problems such as complex experimental process, harsh experimental conditions and unstable diamond nanosheets, especially when graphite transforms into diamond under normal pressure and releases the pressure before being converted into graphene.
The method of catalyzing diamond nanosheets under normal pressure is used to pre-form the two-dimensional titanium carbide and Ni metal powder, argon heating and chlorine etching reaction, and then oxidation and purification in the air, and diamond is formed using high-stress nickel catalyst. Nanosheets.
The synthetic stable diamond nanosheets under mild conditions were achieved, with simple process and low cost. The lateral dimensions and thickness of the nanosheets were in the range of 120-180 nm and 2.67-4.33 nm, and had good stability.
Smart Images

Figure CN119143126A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of novel carbon materials, and in particular relates to a method for catalytically synthesizing diamond nanosheets under normal pressure. Background Art
[0002] Diamond nanosheets combine the excellent properties of bulk diamond and two-dimensional materials, and have excellent heat transfer performance, ultra-low friction, high natural frequency and adjustable band gap. They have potential technical and industrial application prospects in nanophotonics, ultra-sensitive resonator sensors and improving wear resistance. However, the current preparation methods of diamond nanosheets mainly include: top-down method and bottom-up method. The first method is to peel off diamond nanosheets from bulk diamond from top to bottom by dissociating along the bulk diamond (111) crystal plane, and the second method is to grow diamond nanosheets from bottom to top by chemical vapor deposition. However, both methods have problems such as complex experimental process and harsh experimental conditions. In addition, in the prior art, graphene is often directly converted into two-dimensional diamond by means of high pressure and other means. Once the two-dimensional diamond (diamond nanosheet) obtained by this method is released from pressure, it will be converted back into graphene, and the obtained diamond nanosheet is unstable. Therefore, it is necessary to seek other technical means to avoid this problem.
[0003] In the prior art, for example, in the patent application with publication number CN117776173A, the HFCVD system is used to reduce the tantalum wire processing pressure at a relatively low power, and the monodispersed tantalum atoms escaping from the metal tantalum wire are deposited on the surface of the single crystal flake graphite substrate, and then annealing is performed to achieve the transformation of graphite to diamond under normal pressure. For example, in the patent application with publication number CN118062842 A, a tantalum-loaded graphite sample is prepared by a PVD system, and the graphite sample is subjected to hydrogen plasma treatment by an MPCVD system, and then annealing is performed to achieve the transformation of graphite to diamond under normal pressure. Both methods utilize the second method mentioned above to grow diamond nanosheets from bottom to top through chemical vapor deposition, and there are problems of complex experimental process and harsh experimental conditions.
[0004] Therefore, developing a convenient new method to synthesize diamond nanosheets under mild conditions is a research hotspot in this field. Summary of the invention
[0005] In view of the problems existing in the above-mentioned prior art, in order to solve the problems of complex experimental process and harsh experimental conditions in the synthesis of diamond nanosheets, the purpose of the present invention is to design a method for catalytic synthesis of diamond nanosheets at normal pressure and its application, which has the advantage of synthesizing stable diamond nanosheets at normal pressure.
[0006] To achieve the above object, the present invention adopts the following technical solutions:
[0007] In one aspect, the present invention provides a method for catalytically synthesizing diamond nanosheets under normal pressure, comprising the following steps:
[0008] (1) Weigh two-dimensional titanium carbide and Ni metal powder, mix them evenly, pre-press them into a shape, and then compact them to obtain a two-dimensional TiC / Ni compact; during this process, the two-dimensional titanium carbide is prevented from coming into contact with air to cause oxidation reaction.
[0009] (2) placing the two-dimensional TiC / Ni compact in a tube furnace, introducing argon (to expel residual air in the quartz tube), heating (heating is performed under the protection of high-purity argon to avoid oxidation of the two-dimensional titanium carbide during the heating process), turning off the argon and introducing chlorine to perform an etching reaction, while stopping the introduction of chlorine and introducing argon, cooling to room temperature, and obtaining a carbon material with diamond nanosheets;
[0010] (3) Taking the carbon material with diamond nanosheets, heating it in an air atmosphere and maintaining it for oxidation to obtain purified diamond nanosheets, so as to remove the non-diamond phase in the sample.
[0011] In the method for catalytic synthesis of diamond nanosheets under normal pressure, the preparation method of the two-dimensional titanium carbide in step (1) is:
[0012] (a) taking graphite, soaking it in perchloric acid, transferring it to a tube furnace and heating it for reaction to obtain graphene aggregates;
[0013] (b) After mixing and grinding graphene aggregates, metal titanium powder and dry mixed salt, the mixture is heated under an Ar atmosphere for reaction. After the reaction is completed, the mixture is cooled to room temperature, washed, filtered and dried to obtain two-dimensional titanium carbide.
[0014] In the method for catalytic synthesis of diamond nanosheets under normal pressure, the mass volume ratio of graphite to perchloric acid in step (a) is 1:(10-15) g / mL;
[0015] The soaking time is 0.5 to 1.5 hours;
[0016] The conditions for the temperature-raising reaction are: a temperature-raising rate of 3 to 5° C. / min, a temperature rising to 170 to 200° C., and a reaction time of 1 to 1.5 h.
[0017] A method for catalytically synthesizing diamond nanosheets under normal pressure, wherein the mixed salt in step (b) is a mixed salt of sodium chloride and potassium chloride; the sodium chloride and potassium chloride need to be dehydrated in a vacuum drying oven before being mixed with graphene aggregates and metal titanium powder, preferably, the dehydration temperature and time are 140° C. and 12 hours, respectively, otherwise 2D TiC cannot be synthesized.
[0018] The mass ratio of the graphene aggregate, the metal titanium powder and the mixed salt is 0.3:1.2:10.5;
[0019] The conditions for the temperature-raising reaction are: a heating rate of 4 to 5° C. / min, a temperature of 850 to 950° C., and a reaction time of 3 to 5 hours.
[0020] In the method for catalytically synthesizing diamond nanosheets under normal pressure, the mass ratio of sodium chloride to potassium chloride is 1:1.
[0021] In the method for catalytic synthesis of diamond nanosheets under normal pressure, the mass ratio of the two-dimensional titanium carbide and Ni metal powder in step (1) is 1:1-10;
[0022] In the method for catalytic synthesis of diamond nanosheets under normal pressure, the pre-pressing pressure in step (1) is 2 to 8 MPa;
[0023] The compaction conditions are: compaction stress of 5 to 6 GPa, and maintaining the compaction stress for 5 to 10 minutes.
[0024] In the method for catalytic synthesis of diamond nanosheets under normal pressure, the conditions for introducing argon gas in step (2) are: flow rate 300-600 mL / min, time 10-30 min;
[0025] The heating conditions are: heating rate 10-15°C / min, heating to 1000°C;
[0026] The flow rate of the chlorine gas is 30-60 mL / min;
[0027] The etching reaction time is 1.5 to 2.5 hours.
[0028] In the method for catalytic synthesis of diamond nanosheets under normal pressure, the conditions for heating and maintaining the temperature in step (3) are: heating rate of 10°C / min, heating to 475-525°C, and maintaining for 15-20h.
[0029] In a second aspect, the present invention provides the use of any of the methods described above in catalytic synthesis of diamond nanosheets at normal pressure.
[0030] In a third aspect, the present invention provides a diamond nanosheet synthesized by any of the methods described above.
[0031] Compared with the prior art, the present invention has the following beneficial effects:
[0032] The present invention introduces nano-scale nickel powder into the interlayer of 2D TiC in a high stress state by applying compaction stress through a six-sided top press. In the subsequent chlorine etching process, the Ti atoms in the 2D TiC are selectively etched away, and the remaining C atoms are reorganized to form a diamond nanosheet structure under the action of a nickel catalyst in a high stress state. The lateral size range of the diamond nanosheet prepared by the present invention is 120-180nm, and the thickness range is 2.67-4.33nm. The synthesis conditions of the method of the present invention are easy to achieve, the process is simple, and the cost is low. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 The transmission photographs of the diamond nanosheets obtained in Example 1 of the present invention, wherein (a) is a TEM image of the diamond nanosheets; (b) is an HRTEM image of the red box area in Figure a, and the inset is an enlarged HRTEM image of the red dotted box; (c) is an HRTEM image of the blue box area in Figure a, and the inset is an enlarged HRTEM image of the blue dotted box; (d) is an HRTEM image of the green box area in Figure a, and the inset is an enlarged HRTEM image of the green dotted box;
[0034] Figure 2 These are AFM images of the diamond nanosheets obtained in Example 1 of the present invention, wherein (a) is an AFM image of the diamond nanosheets; and (b) is a height curve graph. DETAILED DESCRIPTION
[0035] The technical solution of the present invention will be further explained below in conjunction with embodiments and drawings.
[0036] Embodiment 1:
[0037] (1) In-situ synthesis of 2D TiC: First, 1g of 2000 mesh natural flake graphite was soaked in 10mL of perchloric acid for 1h, then placed in a tube furnace, heated to 200℃ at a heating rate of 5℃ / min, and reacted at this temperature for 1h to obtain graphene aggregates. Graphene aggregates, metal titanium powder and a mixed salt of sodium chloride and potassium chloride (NaCl:KCl=1:1, molar ratio) were mixed and ground in a mass ratio of 0.3g:1.2g:10.5g, and then heated to 900℃ at a heating rate of 5℃ / min in an Ar atmosphere for 3h. After cooling to room temperature, the mixture was washed with deionized water and filtered, and placed in a vacuum drying oven at 80℃ for vacuum drying for 12h to obtain 2D TiC (two-dimensional titanium carbide).
[0038] (2) Preparation of 2D TiC / Ni compacts: 2D TiC (two-dimensional titanium carbide) was used as a precursor and nano-scale nickel powder was used as a catalyst in a mass ratio of 0.25 g:0.75 g. The mixture was evenly mixed in a glove box and loaded into a 9.5 mm diameter cemented carbide mold. The 2D TiC / Ni cylindrical blocks were pre-pressed using a powder tablet press with a pre-forming pressure of 3 MPa. Finally, a 6 GPa compaction stress was applied to the 2D TiC / Ni cylindrical blocks using a six-sided top press and the pressure was maintained for 10 min to obtain a two-dimensional TiC / Ni compact.
[0039] (3) Chlorine etching of 2D TiC / Ni compacts: The 2D TiC / Ni compacts were placed in a tube furnace, and high-purity argon was introduced at a flow rate of 600 mL / min for 10 min. Then, under the protection of the argon atmosphere, the temperature was raised to 1000°C at a rate of 15°C / min. When the temperature in the furnace reached 1000°C, the argon was turned off and chlorine was introduced for etching reaction. The flow rate of chlorine was 30 mL / min, and the etching reaction time was 2 h. After the reaction was completed, the introduction of chlorine was stopped and high-purity argon was introduced. The compacts were cooled to room temperature under the protection of the inert gas argon to obtain a carbon material with a diamond nanosheet structure.
[0040] (3) Air oxidation purification treatment of diamond nanosheets: The carbon material sample with a diamond nanosheet structure obtained by chlorine etching in step 3 is placed in a tubular furnace, and heated to 500°C at a rate of 10°C / min in an air atmosphere and maintained at this temperature for 20 h to remove the non-diamond phase in the sample and obtain diamond nanosheets.
[0041] The diamond nanosheets purified by air oxidation were observed by transmission electron microscopy. Figure 1 shown. Figure 1 A TEM image of a typical diamond nanosheet is shown in a. Figure 1 bd Figure 1 HRTEM images of the areas marked by red, blue and green boxes in a. Figure 1 In the illustrations bd, lattice fringes with a lattice spacing of 0.2060 nm can be clearly observed, which corresponds to the lattice spacing of the cubic diamond (111) crystal plane. Figure 2 This is a typical AFM image of a diamond nanosheet. From the AFM results, it can be concluded that the lateral size of this diamond nanosheet is about 140nm and the thickness is about 4.3nm, which has the typical characteristics of a two-dimensional material.
[0042] Embodiment 2:
[0043] (1) In-situ synthesis of 2D TiC: First, 1g of 2000 mesh natural flake graphite was soaked in 15mL of perchloric acid for 1.5h, then placed in a tube furnace, heated to 170℃ at a heating rate of 3℃ / min, and reacted at this temperature for 1.5h to obtain graphene aggregates. Graphene aggregates, metal titanium powder and a mixed salt of sodium chloride and potassium chloride (NaCl:KCl=1:1, molar ratio) were mixed and ground in a mass ratio of 0.3g:1.2g:10.5g, and then heated to 850℃ at a heating rate of 4℃ / min in an Ar atmosphere for 5h. After cooling to room temperature, it was washed with deionized water and filtered, and placed in a vacuum drying oven at 80℃ for vacuum drying for 12h to obtain 2D TiC (two-dimensional titanium carbide).
[0044] (2) Preparation of 2D TiC / Ni compacts: 2D TiC was used as a precursor and nano-sized nickel powder was used as a catalyst in a mass ratio of 0.25 g:1 g. The mixture was evenly mixed in a glove box and loaded into a 9.5 mm diameter cemented carbide mold. The 2D TiC / Ni cylindrical blocks were pre-pressed using a powder tablet press with a pre-forming pressure of 8 MPa. Finally, a 5 GPa compaction stress was applied to the 2D TiC / Ni cylindrical blocks using a six-sided top press and the pressure was maintained for 5 min to obtain a two-dimensional TiC / Ni compact.
[0045] (3) Chlorine etching of 2D TiC / Ni compacts: The 2D TiC / Ni compacts were placed in a tubular furnace, and high-purity argon was introduced at a flow rate of 300 mL / min for 30 min. Then, under the protection of the argon atmosphere, the temperature was raised to 1000°C at a rate of 10°C / min. When the temperature in the furnace reached 1000°C, the argon was turned off and chlorine was introduced for etching reaction. The flow rate of chlorine was 60 mL / min, and the etching reaction time was 2.5 h. After the reaction was completed, the introduction of chlorine was stopped and high-purity argon was introduced. The compacts were cooled to room temperature under the protection of the inert gas argon to obtain a carbon material with a diamond nanosheet structure.
[0046] (4) Air oxidation purification of diamond nanosheets: The carbon material sample with a diamond nanosheet structure obtained by chlorine etching in step 3 was placed in a tube furnace, heated to 475°C at a rate of 10°C / min in an air atmosphere, and maintained at this temperature for 15 hours to remove the non-diamond phase in the sample. A two-dimensional diamond nanosheet with a structure similar to that of Example 1 was obtained.
[0047] The embodiments of this specific implementation are all preferred embodiments of the present invention, and the protection scope of the present invention is not limited thereto. Therefore, all equivalent changes made according to the structure, shape, principle, etc. of the present invention should be included in the protection scope of the present invention. The optional materials of various components are listed in the specification of the present invention, but those skilled in the art should understand that the enumeration of the above-mentioned component materials is not restrictive or exhaustive, and various components can be replaced by other equivalent materials not mentioned in the specification of the present invention, and the purpose of the present invention can still be achieved. The specific embodiments mentioned in the specification are also only for the purpose of explanation, not to limit the scope of the present invention. In addition, the dosage range of each component of the present invention includes any combination of any lower limit and any upper limit mentioned in the specification, and also includes any range formed by the specific content of the component in each specific embodiment as an upper limit or a lower limit combination: all these ranges are included in the scope of the present invention, but only to save space, these combined ranges are not listed one by one in the specification. Each feature of the present invention listed in the specification can be combined with any other feature of the present invention, and this combination is also within the scope of the disclosure of the present invention, but only to save space, these combined ranges are not listed one by one in the specification.
Claims
1. A method for catalytic synthesis of diamond nanosheets under normal pressure, characterized in that: The following steps are involved: (1) Weighing two-dimensional titanium carbide and Ni metal powder, mixing them evenly, pre-pressing them into a shape, and then compacting them to obtain a two-dimensional TiC / Ni compact; (2) placing the two-dimensional TiC / Ni compact in a tube furnace, introducing argon gas, heating, turning off the argon gas and introducing chlorine gas to perform an etching reaction, stopping the introduction of chlorine gas and introducing argon gas, cooling to room temperature, and obtaining a carbon material with diamond nanosheets; (3) The carbon material having diamond nanosheets is heated and maintained in an air atmosphere for oxidation to obtain purified diamond nanosheets.
2. The method for catalytic synthesis of diamond nanosheets under normal pressure as claimed in claim 1, characterized in that: The preparation method of the two-dimensional titanium carbide in step (1) is: (a) taking graphite, soaking it in perchloric acid, transferring it to a tube furnace and heating it for reaction to obtain graphene aggregates; (b) After mixing and grinding graphene aggregates, metal titanium powder and dry mixed salt, the mixture is heated under an Ar atmosphere for reaction. After the reaction is completed, the mixture is cooled to room temperature, washed, filtered and dried to obtain two-dimensional titanium carbide.
3. The method for catalytic synthesis of diamond nanosheets under normal pressure as claimed in claim 2, characterized in that: The mass volume ratio of graphite to perchloric acid in step (a) is 1:(10-15) g / mL; The soaking time is 0.5 to 1.5 hours; The conditions for the temperature-raising reaction are: a temperature-raising rate of 3 to 5° C. / min, a temperature rising to 170 to 200° C., and a reaction time of 1 to 1.5 h.
4. The method for catalytic synthesis of diamond nanosheets under normal pressure as claimed in claim 2, characterized in that: The mixed salt in step (b) is a mixed salt of sodium chloride and potassium chloride; The mass ratio of the graphene aggregate, the metal titanium powder and the mixed salt is 0.3:1.2:10.5; The conditions for the temperature-raising reaction are: a heating rate of 4 to 5° C. / min, a temperature of 850 to 950° C., and a reaction time of 3 to 5 hours.
5. The method for catalytic synthesis of diamond nanosheets under normal pressure as claimed in claim 4, characterized in that: The mass ratio of the sodium chloride to potassium chloride is 1:
1.
6. The method for catalytic synthesis of diamond nanosheets under normal pressure as claimed in claim 1, characterized in that: The mass ratio of the two-dimensional titanium carbide and Ni metal powder in step (1) is 1:1-10; The pre-pressing pressure is 2-8 MPa; The compaction conditions are: compaction stress of 5 to 6 GPa, and maintaining the compaction stress for 5 to 10 minutes.
7. The method for catalytic synthesis of diamond nanosheets under normal pressure as claimed in claim 1, characterized in that: The conditions for introducing argon in step (2) are: flow rate 300-600 mL / min, time 10-30 min; The heating conditions are: heating rate 10-15°C / min, heating to 1000°C; The flow rate of the chlorine gas is 30-60 mL / min; The etching reaction time is 1.5 to 2.5 hours.
8. The method for catalytic synthesis of diamond nanosheets under normal pressure as claimed in claim 1, characterized in that: The conditions for heating and maintaining the temperature in step (3) are: heating rate 10°C / min, heating to 475-525°C, and maintaining for 15-20h.
9. Use of the method according to any one of claims 1 to 8 in catalytic synthesis of diamond nanosheets under normal pressure.
10. A diamond nanosheet, characterized in that: It is synthesized by the method according to any one of claims 1 to 8.
